Fiscally regressive subsidies and the spatial diffusion of electric vehicles in French cities - Marie Holzer; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2025)
This paper investigates the equity implications of the 2018 policy change regarding France's electric vehicle (EV) subsidies, focusing on its differential impact across French municipalities (i.e., communes) with varying income levels. Using a synthetic event study and a synthetic difference-in-differences approach, a significant and disproportionately lower rate of EV adoption is identified in communes with a higher share of non-taxable (i.e., lower-income) households. Although the nominal subsidy reduction for new EV purchases was the same ( exteuro1,500), the proportional financial burden was larger for lower-income households, thus inhibiting EV uptake compared with higher-income households. Robustness checks-including placebo tests, alternative treatment definitions, and the exclusion of outlier years and regions- support the validity of the causal inference. Additionally, the results show that the exteuro1,000 additional benefit for non-taxable households on secondhand vehicles did not sufficiently offset the impact of the reduction in new EVs. These findings underscore the regressive effects of uniform subsidy cuts across income levels, which may hinder lower-income households from participating equally in the clean energy transition. This work contributes to the literature on environmental equity and offers policy-relevant insights for designing socially inclusive decarbonization strategies amid declining public subsidies across Europe.
Keywords: 330; Electric Vehicle Adoption; France; Subsidy Change; Inequality; Synthetic Difference-in-Differences